The Effect of Victory and Defeat on the Correlations of Stress Parameters Between the Horse and Rider in Kök-Börü Equestrian Teams - Risvanli, Ali; Sen, Ismail; Canuzakov, Kanat; Tulobayev, Askarbek; Tas, Abuzer; Salykov, Ruslan; Ruzikulov, Nuriddin (Wiley, 2025)
The presented study outlines a research plan aimed at determining the effects of winning and losing situations on the relationship levels between the rider and horse's stress, metabolic, and physiological parameters in K & ouml;k-B & ouml;r & uuml;, a traditional equestrian team game. For this purpose, blood samples were collected from both the horses and riders of four different teams participating in two different K & ouml;k-B & ouml;r & uuml; games before and after the games. Cortisol, ACTH, beta-endorphin, epinephrine, norepinephrine, T3 and T4 analyses were performed on the collected blood samples using species-specific commercial ELISA kits. Additionally, biochemical and haematological parameters in the same blood samples were tested using an autoanalyser. Based on the obtained data, it was found that there were both positive and negative correlations between most biochemical and haematological parameters of the winning teams' horses and riders before and after the game. However, when examining the correlations between the hormonal parameters of the winning teams' horses and riders before the game, only a negative correlation was found between ACTH and T4 (-0.529, p < 0.05), and no positive correlation was identified among any hormonal parameters. In conclusion, it was interpreted that in the equestrian team sport of K & ouml;k-B & ouml;r & uuml;, there are significant changes in the hormonal parameters, especially before and after the game, between the horses and riders of the losing teams. Furthermore, it was concluded that winning and losing situations in K & ouml;k-B & ouml;r & uuml; games did not have a significant impact on the correlations between haematological and biochemical parameters before and after the game for both the horses and riders.
Keywords: horse; K & ouml;k-B & ouml;r & uuml;; metabolism; physiology; rider; stress